IDNLearn.com: Where your questions meet expert advice and community support. Get accurate and detailed answers to your questions from our knowledgeable and dedicated community members.

Rewrite the expression with properly formatted variables and equations.

[tex]\[ e) z^3 - 5xy + 3xyz \quad (x=1, y=-1, z=-?) \][/tex]


Sagot :

To solve the given expression [tex]\( z^3 - 5xy + 3xyz \)[/tex] for [tex]\( x = 1 \)[/tex], [tex]\( y = -1 \)[/tex], and [tex]\( z = -1 \)[/tex], let's break it down step-by-step.

1. Calculate [tex]\( z^3 \)[/tex]:
[tex]\[ z = -1 \implies z^3 = (-1)^3 = -1 \][/tex]
Thus, [tex]\( z^3 = -1 \)[/tex].

2. Calculate [tex]\( -5xy \)[/tex]:
[tex]\[ x = 1, y = -1 \implies -5xy = -5 \cdot 1 \cdot -1 = 5 \][/tex]
So, [tex]\( -5xy = 5 \)[/tex].

3. Calculate [tex]\( 3xyz \)[/tex]:
[tex]\[ x = 1, y = -1, z = -1 \implies 3xyz = 3 \cdot 1 \cdot -1 \cdot -1 = 3 \][/tex]
Therefore, [tex]\( 3xyz = 3 \)[/tex].

4. Combine the results:
[tex]\[ z^3 - 5xy + 3xyz = -1 + 5 + 3 \][/tex]

5. Sum up the terms:
[tex]\[ -1 + 5 + 3 = 7 \][/tex]

So, the value of the expression [tex]\( z^3 - 5xy + 3xyz \)[/tex] when [tex]\( x = 1 \)[/tex], [tex]\( y = -1 \)[/tex], and [tex]\( z = -1 \)[/tex] is [tex]\( \boxed{7} \)[/tex].